Desarrollo de estrategias de marketing para mejorar el posicionamiento del hotel malecón INN de la ciudad de Guayaquil, año 2016 - Santillán Loor, Gardenia Annel (2017)
This research project was carried out with the aim of improving the positioning of the Hotel Malecon Inn; analysis of research has allowed him to find the reality of what happens in the market, the relationship between the supply of hotel and customers or guests and their expectations before receiving the service, it is proposed to design a marketing plan which consists in principle of an analysis of the company goals and objectives, then followed the SWOT analysis of the strategies and tactics oriented product, price, distribution and communication. The strategic approach on these raised above key factors will allow the hotel to improve its positioning of both current and potential customers, in addition to direct competitors, which will be consolidated in tourism and hotel offer is today Guayaquileño very narrow in the market…….